Design of Electro Cardiograph Machine Based on Atmega Microcontroller - Bambang Guruh Irianto; Budhiaji Budhiaji; Syaifudin Syaifudin (Institute of Advanced Engineering and Science, 2016)
ECG machine on the market, has a considerable cost, the technology used is still very complicated. In efficient and display ECG still not interconnect with other devices. In this study, the researchers designed ECG machine 12 channels to take advantage ATMega microcontroller technology, Graphic LCD 64x12, which can be obtained on the market at low prices, thus yielding a portable ECG apparatus, can interconnect with other devices and cheap. Objective is to design a ECG machine using ATMega microcontroller technology, by making a series of bio amplifier ECG, measuring the amplitude and frequency response bio amplifier, and make the ECG signal processing circuit with microcontroller, which can be displayed on a 128x64 graphic LCD or PC. To answer the research objectives, the design of the research is to use pure experimental research is the design of experimental series. The independent variable ECG phantom or human and the dependent variable is the ECG machine. While the design ECG machine through the stages as follows: circuit design, circuit testing and calibration output. The conclusion of this study: The result of the design of microcontroller ATMega program listings can be used transform and run the program to the ECG machine to know the number of heartbeats, a beep sound every wave R the ECG signal, displayed on the graphical LCD, PC, printed through a computer, and can be stored in computer.